The Effects of Social Characteristics of Jobs on the Cognitive Skills of Adults in the United States: A PIAAC Analysis. Issue 2 (May 2020) - Lopes, Tobin; Scully-Russ, Ellen; Zarestky, Jill; Collins, Joshua C.
There is contrary research around whether collaboration at work fosters individual learning and skill development. This study's purpose was to examine the relationship between social characteristics of jobs on adults' cognitive skills as measured by the Program for the International Assessment of Adult Competencies (PIAAC). For select industry sectors, we used a linear regression model to predict scores for PIAAC scales—literacy, numeracy, and problem solving in technology-rich environments—based on the independent variables gender, education level, frequency of workplace collaboration, and frequency of sharing work-related information. Results showed level of collaboration at work is negatively associated with PIAAC scores, contradicting current thinking on the role of social interactions in the workplace. We conclude there may be an overemphasis on the social characteristics in job design in some industries and workplaces, leaving little support and time for other activities known to support workplace learning, like management support and time for reflection.